Progress in surface and membrane science. - Cadenhead, David Allan; Danielli, J. F. (James Frederic), 1911-1984 (Academic Press, 1978)
Progress in Surface and Membrane Science, Volume 12 covers the advances in the study of surface and membrane science. The book discusses the topographical differentiation of the cell surface; the NMR studies of model biological membrane system; and an irreversible thermodynamic approach to energy coupling in mitochondria and chloroplasts. The text also describes water at surfaces; the nature of microemulsions; and the energy principle in the stability of interfaces. Biochemists, physicists, chemical engineers, and people involved in surface and coatings research will find the book invaluable.